Regeneration of kaempferia parviflora from Meristem Through Somatic Embryogenesis - Ab Rahman, Zuraida; Ahmad, Nur Auni Syazalien; Basirun, Nur Najwa Arifah; Othman, Ayu Nazreena (European Journal of Applied Sciences, 2023)
The most effective combination of growth regulators for inducing callus formation in the meristem tissue of Kaempferia parviflora was found to be 0.5 mg/L of 6- Benzylaminopurine (BAP) combined with 2.0-5.0 mg/L of Naphthaleneacetic acid (NAA). This combination resulted in the formation of calluses weighing between 5.7 g and 5.8 g. These calluses were predominantly friable and had a yellowish colour. To promote the proliferation of calluses, two different carbon sources, namely sucrose and maltose, were tested. The best results were obtained when using sucrose at a concentration of 30 g/L, supplemented with 0.5 mg/L of Thidiazuron (TDZ) and a range of 1.0-3.0 mg/L of BAP. Under these conditions, the callus weight reached the highest values recorded, ranging from 10.37 g to 11.50 g. Additionally, this medium exhibited the highest efficiency in developing green somatic embryos (2.1-5.5%), with no browning observed, unlike with maltose. For regeneration, the optimal medium consisted of a combination of 5.0 mg/L of NAA, 0.5 mg/L of TDZ, and 1.0 mg/L of BAP. This medium resulted in the highest production of somatic embryos (21.5 g) and the highest number of plantlets (7.8). Overall, the study demonstrated the successful manipulation of media composition to induce callus formation, promote callus proliferation, and achieve efficient somatic embryo production and plantlet regeneration in Kaempferia parviflora.